Punctuation and Text Division in Two Early Narratives: The Tsinghua University *Jin Wen Gong ru yu Jin and Zi Fan Zi Yu Manuscripts. - KRIJGSMAN, RENS (Journal of the American Oriental Society)
Volume 7 of the Tsinghua manuscripts contains multiple historiographical narratives interspersed with punctuation. This article looks into two manuscripts likely prepared in the same workshop and possibly by the same scribe. I examine how punctuation in the manuscripts engages with the structure of the texts, forming a particular reading experience and understanding of the sectioning of the narrative. The article suggests that the use of punctuation in these manuscripts reflects the punctuator's understanding of the narrative divisions and main points of the texts. Far from merely marking individual sentences, the punctuation selectively marks sections and subsections in the narrative, corresponding to changes of interlocutor, scene and setting, and key information supporting a particular reading of the sense of the texts. The punctuator chose to amplify certain aspects of the narrative--for example, advisors outdoing their superiors--by highlighting certain sections of the text more than others. By examining the ways in which punctuation and narrative structure interact in these two case studies, the article aims to understand the complex relation between punctuation and narrative structure. In doing so, it evaluates the potential agency of punctuators in shaping the reading experience of early historiographical narrative texts.